Weekend and off-hour effects on the incidence of cerebral palsy: contribution of consolidated perinatal care - Satoshi Toyokawa; Junichi Hasegawa; Tsuyomu Ikenoue; Yuri Asano; Emi Jojima; Shoji Satoh; Tomoaki Ikeda; Kiyotake Ichizuka; Satoru Takeda; Nanako Tamiya; Akihito Nakai; Keiya Fujimori; et al. (Komiyama Printing Co. Ltd, 2020)
Abstract Objective This study estimated the effects of weekend and off-hour childbirth and the size of perinatal medical care center on the incidence of cerebral palsy. Methods The cases were all children with severe cerebral palsy born in Japan from 2009 to 2012 whose data were stored at the Japan Obstetric Compensation System for Cerebral Palsy database, a nationally representative database. The inclusion criteria were the following: neonates born between January 2009 and December 2012 who had a birth weight of at least 2000 g and gestational age of at least 33 weeks and who had severe disability resulting from cerebral palsy independent of congenital causes or factors during the neonatal period or thereafter. Study participants were restricted to singletons and controls without report of death, scheduled cesarean section, or ambulance transportation. The controls were newborns, randomly selected by year and type of delivery (normal spontaneous delivery without cesarean section and emergency cesarean section) using a 1:10 case to control ratio sampled from the nationwide Japan Society of Obstetrics and Gynecology database. Results A total of 90 cerebral palsy cases and 900 controls having normal spontaneous delivery without cesarean section were selected, as were 92 cerebral palsy cases and 920 controls with emergent cesarean section. A significantly higher risk for cerebral palsy was found among cases that underwent emergent cesarean section on weekends (odds ratio [OR] 1.72, 95% confidence interval [CI] 1.06-2.81) and during the night shift (OR 2.29, 95% CI 1.30-4.02). No significant risk was found among normal spontaneous deliveries on weekends (OR 1.63, 95% CI 0.97-2.73) or during the quasi-night shift (OR 1.26, 95% CI 0.70-2.27). Regional perinatal care centers showed significantly higher risk for cerebral palsy in both emergent cesarean section (OR 2.35, 95% CI 1.47-3.77) and normal spontaneous delivery (OR 2.92, 95% CI 1.76-4.84). Conclusion Labor on weekends, during the night shift, and at regional perinatal medical care centers was associated with significantly elevated risk for cerebral palsy in emergency cesarean section.